Device for detecting plasticity of carbon paste for aluminum and method for characterizing plasticity

CN122900966APending Publication Date: 2026-10-13ZHENGZHOU NON FERROUS METALS RES INST CO LTD OF CHALCO +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611337099.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

这种检测方式虽然简单直观,但存在诸多无法克服的技术缺陷:其一,主观性强,同一糊料由不同操作人员判定的结果往往存在偏差,缺乏统一的判定标准和量化依据;其二,稳定性差和重复性差,检测结果受操作人员手捏力度、手法习惯以及环境温度等因素的显著影响,同一人员对同一糊料的多次判定结果也难以保持一致;其三,无法输出量化数据,糊料塑性的判定结果仅能作为定性的工艺参考,难以为沥青添加量、混捏温度、糊料温度及模具温度等关键工艺参数的精确调控提供可靠的数据支撑;其四,受环境和温度干扰大,高温糊料在取样和检测过程中的温度衰减会显著影响其塑性表现,而现有检测方式无法有效控制这一变量

Benefits of technology

[0007]根据本申请的铝用炭素糊料塑性检测装置,结构简洁,主要部件为主体检测筒、上盖、下导杆和压力显示计,无复杂的电气系统、液压系统或精密光学部件,能够在阳极车间高温、粉尘、振动的恶劣工况下长期稳定工作。整体体积小巧便于携带,单人即可在产线现场独立完成检测操作。导向耐磨衬套的设置在保证上盖垂直滑动的同时减少了部件磨损,延长了装置的使用寿命。第一排气通孔的设置保证了糊料压缩过程中气体的顺畅排出,避免了气泡滞留对形变测量结果的干扰。下导杆的限位板与圆台段底壁的抵接配合设计,使得检测完成后糊料能够便捷地从检测筒上方推出,提高了检测效率并方便了筒体清洁。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122900966A_ABST
    Figure CN122900966A_ABST
Patent Text Reader

Abstract

The application discloses an aluminum carbon paste plasticity detection device and a plasticity characterization method, and relates to the technical field of prebaked anode production for aluminum electrolysis. The aluminum carbon paste plasticity detection device comprises a main detection cylinder, an upper cover, a lower guide rod and a pressure display meter. The main detection cylinder comprises a cylindrical section and a circular table section connected below the cylindrical section, a scale mark is arranged on the outer side wall of the cylindrical section, and a through hole is formed in the bottom wall of the circular table section. The upper cover is slidably arranged in the cylindrical section, a guide wear-resistant bushing is arranged at the periphery of the upper cover, and a first exhaust through hole is formed in the center of the upper cover. The lower guide rod comprises a limiting plate and a rod body, the rod body is arranged in the through hole and is in sliding fit, and the limiting plate is arranged in the main detection cylinder and abuts against the bottom wall of the circular table section. The pressure display meter is arranged on the top surface of the upper cover and is used for detecting the pressure value. The device is simple in structure and convenient to carry, can quickly complete paste plasticity detection in a high-temperature dust workshop environment, and can output a quantitative plasticity index for process control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of prebaked anode production technology for aluminum electrolysis, and particularly relates to a device for testing the plasticity of carbon paste for aluminum and a method for characterizing plasticity. Background Technology

[0002] Prebaked anodes, as the core component of aluminum electrolysis cells, are hailed as the "heart" of these cells, and their quality directly determines the efficiency, energy consumption, cost, and product quality of aluminum electrolysis production. With the rapid development of the aluminum electrolysis industry towards high efficiency, energy saving, and carbon reduction, higher requirements are being placed on the quality of prebaked anodes. The mixing and molding of carbon paste is a crucial process in the production of prebaked anodes. The plasticity of the paste, as the core link connecting formula design, mixing control, molding process, and subsequent roasting and use effects, directly determines the molding quality of the anode green and the yield rate of the finished product.

[0003] Currently, the carbon industry's testing of paste plasticity remains at the stage of manual sensory judgment, whereby on-site operators subjectively grade the plasticity of the paste by hand, kneading, and pressing. While this testing method is simple and intuitive, it suffers from several insurmountable technical drawbacks: First, it is highly subjective; the results of different operators judging the same paste often differ, lacking a unified judgment standard and quantitative basis. Second, it suffers from poor stability and repeatability; the test results are significantly affected by factors such as the operator's hand pressure, technique, and ambient temperature, and it is difficult for the same person to maintain consistent results on the same paste multiple times. Third, it cannot output quantitative data; the results of paste plasticity judgment can only serve as a qualitative process reference, making it difficult to provide reliable data support for the precise control of key process parameters such as asphalt addition amount, kneading temperature, paste temperature, and mold temperature. Fourth, it is highly susceptible to environmental and temperature interference; the temperature decay of high-temperature pastes during sampling and testing significantly affects their plasticity, and existing testing methods cannot effectively control this variable.

[0004] In summary, current technologies lack a rapid on-site detection solution for the plasticity of prebaked anode paste that meets the quality control requirements of continuous industrial production. Specifically, this requires a portable testing device and method capable of quickly obtaining quantitative indicators of paste plasticity after high-temperature mixing and discharging, even under harsh workshop conditions. This technological gap severely restricts the digital closed-loop control of the prebaked anode production process and further homogenization of product quality. Summary of the Invention

[0005] This application aims to address at least one of the technical problems existing in the prior art. To this end, this application proposes a plasticity testing device and a plasticity characterization method for aluminum carbon paste. The device has a simple structure, is resistant to dust and high temperatures, and is easy to operate. It is suitable for rapid on-site testing under harsh workshop conditions and can objectively and quantitatively characterize the plasticity of the paste, providing data support for subsequent process parameter adjustments.

[0006] In a first aspect, this application provides a device for testing the plasticity of carbon paste for aluminum, comprising: The main detection cylinder includes a cylindrical section and a frustum section connected below the cylindrical section. The outer wall of the cylindrical section is provided with scale markings along its axial direction. The large end of the frustum section faces upward and is connected to the cylindrical section. A through hole is opened on the bottom wall of the frustum section. The top cover is slidably set inside the cylindrical section of the main detection cylinder. The diameter of the top cover is matched with the inner diameter of the cylindrical section. A guide wear-resistant bushing is provided around the periphery of the top cover, and a first exhaust hole is opened in the center of the top cover. The lower guide rod includes a limiting plate and a rod body connected to the limiting plate. The rod body passes through the through hole in the bottom wall of the frustum section and slides in fit with the through hole. The limiting plate is set inside the main detection cylinder and abuts against the bottom wall of the frustum section. A pressure gauge is installed on the top surface of the cover to detect the pressure applied to the cover.

[0007] The aluminum carbon paste plasticity testing device according to this application has a simple structure. Its main components are the main testing cylinder, upper cover, lower guide rod, and pressure gauge. It lacks complex electrical systems, hydraulic systems, or precision optical components, enabling long-term stable operation under harsh conditions of high temperature, dust, and vibration in the anode workshop. Its compact size makes it easy to carry, allowing a single person to independently complete the testing operation on the production line. The wear-resistant guide bushing ensures vertical sliding of the upper cover while reducing component wear and extending the device's service life. The first exhaust port ensures smooth gas discharge during paste compression, preventing air bubble retention from interfering with deformation measurement results. The abutment design between the lower guide rod's limiting plate and the bottom wall of the frustum section allows the paste to be easily pushed out from the top of the testing cylinder after testing, improving testing efficiency and facilitating cylinder cleaning.

[0008] According to one embodiment of this application, the outer wall of the cylindrical section of the main detection cylinder has multiple scale markings evenly distributed circumferentially.

[0009] According to one embodiment of this application, a travel limit block and a locking alarm component are provided inside the cylindrical section. The travel limit block is spaced apart from the upper end of the cylindrical section by a preset distance. When the upper cover moves to the travel limit block, the locking alarm component triggers an alarm.

[0010] According to one embodiment of this application, the lower guide rod is provided with a second vent hole that penetrates the limiting plate and the rod body.

[0011] According to one embodiment of this application, the diameter of the upper cover is 30mm~200mm, the diameter of the exhaust hole in the center of the upper cover is 3mm~20mm; the inner diameter of the cylindrical section of the main detection cylinder is 31mm~201mm, the height of the cylindrical section is 10mm~100mm; and the diameter of the lower guide rod is 10mm~100mm.

[0012] According to one embodiment of this application, a detachable heat insulation sleeve is provided on the outer wall of the cylindrical section of the main detection cylinder, and the heat insulation sleeve covers the entire outer wall of the main detection cylinder.

[0013] Secondly, this application provides a method for characterizing the plasticity of carbon paste for aluminum, employing any of the technical solutions in the first aspect, and the method for characterizing the plasticity of carbon paste for aluminum includes the following steps: Step 1: Take the paste that has just finished the kneading operation out of the self-mixing production line and put the paste into the main detection cylinder within 5 seconds, so that the paste completely fills the internal space of the main detection cylinder. Step 2: Close the top cover, select at least 3 scale points along the outer circumference of the cylindrical section of the main detection cylinder, read the initial scale value X1 of each scale point, and take the arithmetic mean. Step 3: Apply a fixed force F to the paste through the top cover. After the pressure is applied, keep it still until the top cover stops sliding completely. Step 4: After the top cover stops sliding, select at least 3 scale points along the outer circumference of the cylindrical section of the main body detection cylinder, read the end scale value of each scale point x2, and take the arithmetic mean. Step 5: Remove the paste from the main testing cylinder and weigh the paste mass M; Step 6: Calculate the plasticity index Y according to the formula Y=K·[M / (F·π·R²)·(X1-X2)], where K is the proportionality coefficient and R is the inner radius of the cylindrical section of the main testing cylinder.

[0014] The method for characterizing the plasticity of aluminum carbon paste according to this application is simple to operate, and operators can complete the operation according to the standardized procedure without long-term experience training. The entire process from high-temperature sampling to outputting the plasticity index Y can be completed within 30 seconds, and the detection efficiency is far higher than that of traditional laboratory analysis methods. Through multiple quality control measures such as averaging of circumferential multi-point scale readings, paste quality correction, cross-sectional area standardization, and parallel test verification, the accuracy, repeatability, and comparability of the test data are guaranteed. As a single numerical quantitative evaluation index, the plasticity index Y can intuitively distinguish the three states of paste: dry, suitable, and viscous, solving the technical problems of strong subjectivity, poor stability, and lack of quantitative data support caused by the industry's long-term reliance on human sensory judgment. The plasticity index Y can be connected to the DCS or MES system of the production workshop to dynamically adjust key process parameters such as asphalt addition, kneading temperature, paste temperature, and mold temperature, realizing digital closed-loop control of paste plasticity.

[0015] According to one embodiment of this application, the fixed force F is 0.1N~150N; the sliding distance of the top cover is 0~50mm. When the sliding distance of the top cover exceeds 50mm, the current test is deemed to be invalid and a retest is required.

[0016] According to one embodiment of this application, the proportionality coefficient K ranges from 0.1 to 10, and the K value is set according to the kneading process of the aluminum carbon production line; the paste mass M is weighed using a weighing scale with an accuracy of 0.01g.

[0017] According to one embodiment of this application, the method for characterizing the plasticity of carbon paste for aluminum further includes a parallel test verification step: continuously test two sets of parallel samples of the same output paste, calculate the relative deviation of the two sets of plasticity index Y values, and determine the test data as valid when the relative deviation is ≤5% and resample and retest when the relative deviation is >5%.

[0018] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0019] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 This is a schematic diagram of the structure of the aluminum carbon paste plasticity testing device provided in the embodiments of this application; Figure 2 This is a top view schematic diagram of the plasticity testing device for aluminum carbon paste provided in the embodiments of this application; Figure 3 yes Figure 2 Sectional view at point AA; Figure 4 yes Figure 2 A cross-sectional view of point AA in another state; Figure 5 This is a schematic flowchart of the method for characterizing the plasticity of carbon paste for aluminum provided in the embodiments of this application.

[0020] Figure label: 100. Aluminum Carbon Paste Plasticity Testing Device; 1. Main Testing Cylinder; 11. Cylindrical Section; 12. Frustum Section; 2. Top Cover; 21. First Exhaust Hole; 3. Lower Guide Rod; 31. Limiting Plate; 32. Rod Body; 33. Second Exhaust Hole; 4. Pressure Display Gauge. Detailed Implementation

[0021] The embodiments of this application are described in detail below. Examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain this application, and should not be construed as limiting this application.

[0022] The following is for reference. Figures 1-5 This application describes a plasticity testing apparatus and a plasticity characterization method for aluminum carbon paste according to embodiments of the present application.

[0023] Please see Figure 1 , Figure 2 , Figure 3 and Figure 4 This application provides a plasticity testing device 100 for aluminum carbon paste, which includes a main testing cylinder, an upper cover 2, a lower guide rod 3, and a pressure display gauge 4.

[0024] The main detection cylinder includes a cylindrical section 11 and a frustum section 12 connected below the cylindrical section 11. The cylindrical section 11 is a cylindrical structure of equal diameter, and its internal space serves as the main chamber for paste compression. The inner wall surface of the cylindrical section 11 also serves as the guide surface for the sliding of the upper cover 2. The inner wall of the cylindrical section 11 should be smooth and flat to reduce the frictional resistance during the sliding process of the upper cover 2 and ensure that the upper cover 2 is only subjected to vertical pressure and is not affected by lateral interference forces.

[0025] The larger end of the frustum section 12 faces upward and connects to the lower end of the cylindrical section 11, while the smaller end of the frustum section 12 faces downward, forming an overall conical structure that is wider at the top and narrower at the bottom. The advantage of this composite cylindrical structure is that when the paste is loaded into the testing cylinder, it can smoothly fall to the bottom under gravity and fill the entire cavity. After the test is completed, the operator can push the compacted paste out from the top of the testing cylinder through the lower guide rod 3. The conical inner wall of the frustum section 12 facilitates the demolding of the paste.

[0026] The bottom wall of the frustum section 12 has a through hole for the lower guide rod 3 to pass through and slide with it.

[0027] In some embodiments, the cylindrical segment 11 and the frustum segment 12 can be manufactured using a one-piece molding process, such as integral turning or integral casting followed by finishing, to ensure the connection strength, coaxiality, and continuity of the inner wall between the two.

[0028] In other embodiments, the cylindrical segment 11 and the frustum segment 12 can also be processed separately and then fixedly connected together by welding.

[0029] The outer wall of the cylindrical segment 11 is provided with a scale mark along its axial direction. The scale mark extends along the length of the cylindrical segment 11 and is used to read the axial position of the upper cover 2 during the sliding process.

[0030] The graduation value of the scale mark directly affects the accuracy of the reading. In some embodiments, the graduation value of the scale mark is 1 mm. In other embodiments, the graduation value of the scale mark can be 0.5 mm. In still other embodiments, the graduation value of the scale mark can be 2 mm. The starting position of the scale mark can be calibrated according to actual needs, for example, using the upper end face of the cylindrical section 11 as the reference zero point, or using a preset filling height position as the reference zero point.

[0031] The upper cover 2 is slidably disposed within the cylindrical section 11 of the main detection cylinder, and the diameter of the upper cover 2 is adapted to the inner diameter of the cylindrical section 11. An appropriate clearance should be maintained between the upper cover 2 and the inner wall of the cylindrical section 11. This ensures that the upper cover 2 can smoothly slide downwards along the axial direction of the cylindrical section 11 under external force, while preventing the upper cover 2 from tilting or deflecting during sliding due to excessive clearance. In some embodiments, the one-sided clearance between the upper cover 2 and the inner wall of the cylindrical section 11 is 0.5 mm. In other embodiments, this one-sided clearance can be 1 mm. In still other embodiments, this one-sided clearance can be 2 mm. The top surface of the upper cover 2 is the force-applying surface, used to receive the externally applied fixed pressure and uniformly transmit this pressure to the paste below. The bottom surface of the upper cover 2 is the working surface, in direct contact with the paste and converting the pressure into a compressive force on the paste.

[0032] A guide wear-resistant bushing is provided around the periphery of the upper cover 2. The guide wear-resistant bushing is set on the outer peripheral surface of the upper cover 2 and directly contacts the inner wall of the cylindrical section 11 when the upper cover 2 slides along the inner wall of the cylindrical section 11. The guide wear-resistant bushing has two functions: firstly, it guides the upper cover 2 to always move vertically through the sliding fit between the bushing and the inner wall of the cylindrical section 11, avoiding eccentric tilting of the upper cover 2 due to uneven force during paste compression, thereby eliminating deformation errors caused by lateral tilting; secondly, it is wear-resistant. The upper cover 2 needs to slide repeatedly during frequent testing. Direct metal-to-metal contact can easily lead to accelerated wear and affect the fitting accuracy. The wear-resistant bushing can effectively reduce the wear between the upper cover 2 and the inner wall of the cylinder, extending the service life of the device.

[0033] In some embodiments, the guide wear-resistant bushing is made of a self-lubricating copper alloy, which has excellent wear resistance and self-lubricating properties. In other embodiments, the guide wear-resistant bushing can be made of polytetrafluoroethylene (PTFE). In still other embodiments, the guide wear-resistant bushing can be made of nylon engineering plastic.

[0034] The guide wear-resistant bushing can be inserted into the annular mounting groove around the periphery of the upper cover 2 by interference fit, or it can be fixed to the periphery of the upper cover 2 by screws. Multiple guide wear-resistant bushings can be arranged along the circumference of the upper cover 2 to ensure uniform guidance.

[0035] A first vent hole is provided at the center of the upper cover 2, extending axially through the top and bottom surfaces of the upper cover 2 and connecting the paste chamber to the outside atmosphere. During the mixing process, the paste will contain a certain amount of gas. Simultaneously, the asphalt components in the high-temperature paste will generate volatile gases during heating. When the paste undergoes compression deformation under the pressure of the upper cover 2, these gases will escape from the paste. If the escaped gas cannot be discharged in time, it will form closed air bubbles inside the paste. This affects the compression deformation behavior of the paste, leading to inaccurate deformation measurements. Furthermore, the expansion of these bubbles after depressurization will cause the paste to rebound, further interfering with the measurement results. The first vent hole provides a channel for these gases to escape from the paste chamber, ensuring smooth gas escape during compression.

[0036] In some embodiments, the diameter of the first venting orifice is 5 mm. In other embodiments, the diameter of the first venting orifice can be 3 mm. In still other embodiments, the diameter of the first venting orifice can be 8 mm. The orifice diameter of the first venting orifice can be adaptively adjusted according to the particle size distribution of the paste. For fine-particle pastes, smaller venting orifices can be provided to prevent paste particles from being squeezed out of the venting orifices, while for coarse-particle pastes, larger venting orifices can be provided to ensure smooth venting.

[0037] The lower guide rod 3 includes a limiting plate 31 and a rod 32 connected to the limiting plate 31. The rod 32 passes through a through hole in the bottom wall of the frustum section 12 and slides in fit with the through hole. The outer diameter of the rod 32 matches the diameter of the through hole. The lower end of the rod 32 extends from the bottom of the detection cylinder, and the operator can control the up and down movement of the rod 32 by pushing and pulling the lower end of the rod 32.

[0038] A limiting plate 31 is connected to the upper end of the rod 32 and is disposed inside the main detection cylinder. The outer diameter of the limiting plate 31 is larger than the diameter of the through hole in the bottom wall of the frustum section 12. The limiting plate 31 forms an abutting fit with the bottom wall of the frustum section 12. When the operator pushes the rod 32 upward, the limiting plate 31 moves upward and pushes the paste above it, so that the compacted paste can be pushed out of the detection cylinder from the top by the limiting plate 31. The abutting relationship between the limiting plate 31 and the bottom wall also has a limiting function to prevent the rod 32 from coming out of the through hole.

[0039] Because the rod 32 extends outside the main detection cylinder, staff can operate it by holding the rod 32 during actual use, making the operation more convenient.

[0040] In some embodiments, the limiting plate 31 and the rod 32 are integrally formed. In other embodiments, the limiting plate 31 and the rod 32 can be machined separately and then fixed together by threaded connection. In still other embodiments, the limiting plate 31 and the rod 32 can be fixed together by welding.

[0041] Pressure gauge 4 is located on the top surface of the upper cover 2 and is used to detect the pressure applied to the upper cover 2. By observing the reading of pressure gauge 4, the operator can accurately control the magnitude of the constant force F applied to the upper cover 2, ensuring that the pressure conditions applied are consistent each time.

[0042] The pressure gauge 4 can be a digital pressure sensor, which has the advantages of intuitive readings, high accuracy, and fast response. The digital pressure sensor can lock the applied force value in real time, facilitating reading and recording by the operator. In some embodiments, the pressure gauge 4 has an accuracy of 0.1N. In other embodiments, the pressure gauge 4 has an accuracy of 0.01N.

[0043] Please see Figure 3 and Figure 4 , Figure 3 The diagram shows the upper cover 2 in its unpressed state; Figure 4A schematic diagram of the state after the upper cover 2 is pressed down is shown. In actual operation, high-temperature paste is filled into the main detection cylinder. Under the action of a fixed pressure F, the upper cover 2 slides downward along the inner wall of the cylindrical section 11. The paste undergoes compression deformation under pressure, with internal asphalt flowing and aggregate particle gaps being compressed, resulting in irreversible plastic deformation. During the downward sliding process of the upper cover 2, the guide wear-resistant bushings around the periphery of the upper cover 2 slide against the inner wall of the cylindrical section 11 to ensure the vertical movement of the upper cover 2. The first exhaust hole at the center of the upper cover 2 continuously discharges the gas escaping from the paste during the compression process. The lower guide rod 3 is in a free state during this process, and its rod body 32 slides downward as the volume of the paste shrinks. When the paste reaches the compression equilibrium state, the upper cover 2 stops sliding. At this time, the sliding distance of the upper cover 2 is characterized by the difference between the initial scale value X1 and the final scale value X2. This difference reflects the compressibility of the paste under a fixed pressure. The larger the deformation, the more fully the asphalt is impregnated in the paste, the better its fluidity and plasticity; the smaller the deformation, the lower the asphalt content or the uneven distribution of asphalt, the dry and loose aggregate, and the worse the plasticity. After the test is completed, the operator pushes the rod 32 of the lower guide rod 3 upwards, and the limiting plate 31 pushes the compacted paste out from the top of the testing cylinder, making it easy to remove the paste for subsequent weighing.

[0044] The aluminum carbon paste plasticity testing device 100 provided in this embodiment has a simple structure. Its main components are the main testing cylinder, upper cover 2, lower guide rod 3, and pressure gauge 4. It lacks complex electrical systems, hydraulic systems, or precision optical components, enabling long-term stable operation under harsh conditions of high temperature, dust, and vibration in the anode workshop. Its compact size makes it easy to carry, allowing a single person to independently complete the testing operation on the production line. The guide wear-resistant bushing ensures vertical sliding of the upper cover 2 while reducing component wear and extending the device's service life. The first exhaust port ensures smooth gas discharge during paste compression, preventing air bubble retention from interfering with deformation measurement results. The abutment design between the limiting plate 31 of the lower guide rod 3 and the bottom wall of the frustum section 12 allows the paste to be easily pushed out from the top of the testing cylinder after testing, improving testing efficiency and facilitating cylinder cleaning.

[0045] According to some embodiments of this application, the outer wall of the cylindrical section 11 of the main detection cylinder has multiple scale markings evenly distributed circumferentially.

[0046] Multiple scale markings are evenly distributed circumferentially along the outer wall of the cylindrical section 11, allowing operators to read the scale values ​​corresponding to the top cover 2 from different angles around the cylinder. During the paste compression process, the top cover 2 may tilt slightly due to the anisotropy of the paste or uneven stress, which may result in deviations in the scale values ​​read from a single angle. By reading the scale values ​​at multiple angles and taking the arithmetic mean, the reading eccentricity error caused by the tilt of the top cover 2 can be effectively eliminated, improving the accuracy of the test data.

[0047] In some embodiments, the number of scale marks can be three, evenly distributed at equal angles of 120° along the circumference of the outer wall of the cylindrical segment 11. Using three scale marks ensures comprehensive reading correction without compromising ease of reading and calculation efficiency due to excessive scale density. In other embodiments, the number of scale marks can be four, evenly distributed at 90° along the circumference. In still other embodiments, the number of scale marks can be six, evenly distributed at 60° along the circumference; more scale marks further improve the accuracy of the reading.

[0048] According to some embodiments of this application, a travel limit block and a locking alarm component may be provided inside the cylindrical segment 11. The travel limit block is spaced apart from the upper end of the cylindrical segment 11 by a preset distance. When the upper cover 2 moves to the travel limit block, the locking alarm component triggers an alarm.

[0049] The travel limit block is fixedly installed on the inner wall of the cylindrical section 11, and its installation position determines the maximum downward sliding stroke of the upper cover 2. When the upper cover 2 slides downward to contact the travel limit block during paste compression, it indicates that the sliding distance of the upper cover 2 has reached the preset maximum limit value. At this time, the locking alarm component triggers an alarm to notify the operator that the detection has failed. This design is used to prevent invalid detection data from being generated due to insufficient paste filling causing the upper cover 2 to slide beyond the normal range.

[0050] In some embodiments, the distance between the travel limit block and the upper end of the cylindrical section 11 is 50mm. When the sliding distance of the upper cover 2 exceeds 50mm, it indicates that the paste filling amount is too small or the paste has too good plasticity, and the current test data is unusable, requiring resampling and testing. In other embodiments, this distance can be 40mm. In still other embodiments, this distance can be 60mm. The locking alarm component can adopt a mechanical alarm structure, such as a spring-triggered buzzer or alarm light. In other embodiments, the locking alarm component can use a photoelectric sensor in conjunction with an audible and visual alarm to achieve non-contact automatic detection and alarm.

[0051] Please see Figure 2 , Figure 3 and Figure 4 According to some embodiments of this application, the lower guide rod 3 is provided with a second exhaust hole that penetrates the limiting plate 31 and the rod body 32.

[0052] The second vent hole extends axially along the lower guide rod 3, with one end opening onto the top surface of the limiting plate 31 and communicating with the interior of the main detection cylinder, and the other end opening onto the lower end face of the rod 32 and communicating with the outside atmosphere. The second vent hole cooperates with the first vent hole on the upper cover 2 to form a gas discharge channel during the paste compression process. When the paste is compressed, the gas inside the paste can enter the second vent hole from the area near the top surface of the limiting plate 31, flow axially downwards along the rod 32, and be discharged to the outside atmosphere from the lower end of the rod 32. By setting two vent holes, the path for gas to exit from the paste chamber is more unobstructed, avoiding the problem of air bubble retention caused by poor venting.

[0053] The diameter of the second vent hole can be 2mm, 3mm, 5mm, or other values ​​between 2mm and 5mm. The specific diameter can be adjusted according to the particle size distribution of the paste. For fine-particle pastes, smaller vent holes can be provided to prevent paste particles from clogging the vent holes. The diameter of the second vent hole is usually the same as or slightly smaller than that of the first vent hole to ensure smooth venting while preventing paste particles from leaking out.

[0054] According to some embodiments of this application, the diameter of the upper cover 2 is 30mm to 200mm, and the diameter of the exhaust hole at the center of the upper cover 2 is 3mm to 20mm. The inner diameter of the cylindrical section 11 of the main detection cylinder is 31mm to 201mm, and the height of the cylindrical section 11 is 10mm to 100mm. The diameter of the rod body 32 of the lower guide rod 3 is 10mm to 100mm.

[0055] The diameter of the upper cover 2 determines the contact area between the upper cover 2 and the paste, thus affecting the pressure exerted on the paste under the same pressure. The larger the diameter of the upper cover 2, the smaller the pressure on the paste under the same constant force F, and the smaller the compressibility deformation. Therefore, the selection of the diameter of the upper cover 2 should match the selection of the constant force F to ensure that the paste produces appropriate deformation during the testing process. The diameter of the upper cover 2 can be 49mm, 99mm, 150mm, or other values ​​between 30mm and 200mm.

[0056] The diameter of the vent hole in the center of the top cover 2 determines the smoothness of gas venting. If the diameter of the vent hole is too small, it will lead to poor venting and gas stagnation inside the paste. If the diameter is too large, it may cause asphalt or fine particles in the paste to be squeezed out of the vent hole. The diameter of the vent hole in the center of the top cover 2 can be 2mm, 5mm, 10mm or other values ​​between 3mm and 20mm.

[0057] The inner diameter of the cylindrical section 11 determines the cross-sectional area of ​​the paste filling, thus affecting the pressure exerted on the paste under the same pressure. The larger the inner diameter of the cylindrical section 11, the lower the pressure exerted on the paste under the same pressure. The inner diameter of the cylindrical section 11 is also adapted to the diameter of the upper cover 2, which is slightly smaller than the inner diameter of the cylindrical section 11 to ensure smooth sliding. The inner diameter of the cylindrical section 11 can be 50mm, 100mm, 150mm, or other values ​​between 31mm and 201mm.

[0058] The height of the cylindrical section 11 determines the initial filling height of the paste, which is an important parameter affecting the measurement range of the paste's compression deformation. The greater the height of the cylindrical section 11, the greater the initial filling amount of the paste, and the larger the stroke range of the upper cover 2 during the compression process. The height of the cylindrical section 11 can be 40mm, 50mm, 80mm, or other values ​​between 10mm and 100mm.

[0059] The diameter of the lower guide rod 3 (rod body 32) determines its rigidity and the fit clearance between it and the through hole in the bottom wall of the frustum section 12. A larger diameter of rod body 32 results in better rigidity and reduces the likelihood of bending deformation when pushing the paste to demold. The diameter of rod body 32 can be 20mm, 30mm, 60mm, or other values ​​between 10mm and 100mm, specifically selected based on the overall dimensions of the detection cylinder and the degree of paste compaction.

[0060] According to some embodiments of this application, a detachable heat insulation sleeve is provided on the outer wall of the cylindrical section 11 of the main detection cylinder, and the heat insulation sleeve covers the entire outer wall of the main detection cylinder.

[0061] Thermal insulation jackets are used to reduce the heat exchange rate between the high-temperature asphalt and the ambient air during asphalt sampling and testing, thus slowing down the temperature drop of the asphalt. The plasticity of the asphalt is closely related to its temperature; a decrease in temperature leads to an increase in asphalt viscosity, making the asphalt harder and more brittle, and significantly altering its compression deformation behavior. If the temperature of the asphalt drops too quickly during sampling and testing, the test results will not accurately reflect the original plastic state of the asphalt during mixing and discharging. The thermal insulation jacket effectively prolongs the time the asphalt maintains its original temperature, ensuring the accuracy of the test results.

[0062] The thermal insulation jacket features a detachable design, allowing operators to flexibly choose whether to use it based on the workshop ambient temperature, and also facilitating daily cleaning and maintenance of the testing cylinder. The jacket can be made of aluminum silicate fiber felt, fiberglass wool, aerogel felt, or other materials with good high-temperature resistance and thermal insulation properties, with thicknesses of 5mm, 10mm, 15mm, 20mm, or other thicknesses selected according to actual insulation requirements. The inner diameter of the jacket matches the outer diameter of the cylindrical section 11, fitting snugly against the outer wall of the cylinder after installation. To avoid interfering with the reading of the scale markings, a transparent observation window can be provided on the jacket corresponding to the scale markings, allowing operators to read the values. Alternatively, the jacket can be segmented, with a hinged observation cover at the corresponding scale marking location. The cover is opened when reading the value and closed afterward to maintain insulation. The jacket can also be installed only in a portion of the cylindrical section 11, avoiding the scale marking area.

[0063] Please see Figure 5 Based on the same concept, this application also provides a method for characterizing the plasticity of carbon paste for aluminum, which uses the aluminum carbon paste plasticity testing device 100 in any of the above embodiments and includes the following steps.

[0064] Step 1: Remove the paste from the self-mixing production line after the mixing operation and place it into the main testing cylinder within 5 seconds, ensuring the paste completely fills the internal space of the cylinder. During sampling, avoid squeezing or kneading the paste to prevent premature plastic deformation that could interfere with the test results. Immediately after sampling, place the paste into the testing cylinder, ensuring it completely fills the internal space of the cylindrical section 11 and frustum section 12 of the testing cylinder, without any gaps, layering, or air bubbles. Controlling the sampling time to within 5 seconds minimizes heat loss from the high-temperature paste during sampling and filling, ensuring the test results accurately reflect the plastic state of the paste at the time of mixing and discharging.

[0065] Step 2: Close the top cover 2. Select at least 3 scale points along the circumference of the outer wall of the cylindrical section 11 of the main detection cylinder, and read the initial scale value X1 of each scale point. Take the arithmetic mean. After the top cover 2 is closed, its bottom surface will be in contact with the top surface of the paste. The scale value X1 read at this time represents the initial height of the paste in its uncompressed state. Averaging multiple readings can effectively eliminate reading eccentricity error. The number of reading points can be 3, 4, 6 or more. When 3 points are set, they should be evenly distributed along the circumference.

[0066] Step 3: Apply a constant force F to the paste through the upper cover 2. After the pressure is applied, keep it stationary until the upper cover 2 completely stops sliding. The pressure should be applied at a uniform speed to avoid deformation distortion of the paste caused by instantaneous impact force. After the pressure stabilizes, the upper cover 2 gradually slides downward under the combined action of the elastic response and plastic rheology of the paste. When the paste reaches the compression equilibrium state, the upper cover 2 completely stops.

[0067] Step 4: After the top cover 2 stops sliding, select at least 3 scale points along the outer circumference of the cylindrical section 11 of the main body detection cylinder, read the termination scale value X2 of each scale point, and take the arithmetic mean.

[0068] Step 5: Remove the paste from the main testing cylinder and weigh the paste mass M. All paste should be removed to avoid residue adhering to the inner wall of the cylinder and affecting weighing accuracy.

[0069] Step 6: Calculate the plasticity index Y according to the formula Y=K·[M / (F·π·R²)·(X1-X2)], where K is the proportionality coefficient and R is the inner radius of the cylindrical section 11 of the main detection cylinder.

[0070] In the above formula, M represents the paste mass, used to correct for differences in paste density caused by different operators' filling techniques; FπR² represents the pressure exerted on the paste, where F is a constant force, R is the inner radius of the cylindrical segment 11, and πR² is the pressure-bearing area of ​​the paste; (X1-X2) represents the compressibility deformation of the paste under constant pressure. By introducing the paste mass M and the pressure-bearing area πR² for standardization, the plasticity index Y obtained between different filling conditions and different specifications of testing devices is comparable. The proportionality coefficient K is used to adapt to the process differences of different production lines, such as the differences between continuous kneading and intermittent kneading production lines, and between different aggregate particle size formulations, all of which can be corrected by the K value.

[0071] The above-mentioned testing method can complete the entire process from sampling to outputting the plasticity index Y within 30 seconds, which can meet the needs of rapid testing in industrial settings.

[0072] According to some embodiments of this application, the set force F is 0.1N to 150N. The selection of the set force F should match the cross-sectional area of ​​the testing cylinder and the plasticity range of the paste. If the set force F is too small, it may lead to insufficient compression of the paste and insignificant deformation, thus affecting the measurement accuracy. If the set force F is too large, it may lead to over-compaction of the paste or even the extrusion of asphalt from the aggregate surface, which will also affect the accuracy of the test results. The set force F can be 50N, 80N, 100N, or other values ​​between 0.1N and 150N.

[0073] The sliding distance of the upper cover 2 is 0~50mm. When the sliding distance of the upper cover 2 exceeds 50mm, the current test is deemed invalid and a retest is required. The sliding distance of the upper cover 2 is calculated from the difference between the initial scale value X1 and the final scale value X2, representing the compressibility deformation of the paste under a constant pressure. When the sliding distance exceeds 50mm, it indicates that the paste filling amount is insufficient or the plasticity of the paste does not match the currently used test parameters, and resampling and testing are required.

[0074] According to some embodiments of this application, the proportionality coefficient K ranges from 0.1 to 10, and the K value is set according to the kneading process of the aluminum carbon production line. Different kneading processes have a significant impact on the microstructure and plasticity of the paste. In continuous kneading processes, the shearing action on the paste is more continuous and uniform, while in intermittent kneading processes, the kneading effect of the paste is greatly affected by the kneading time and batch. Therefore, it is necessary to pre-calibrate a suitable K value for the specific production line process and aggregate particle size distribution. The K value can be 0.5, 1, 1.5, 2, or other values ​​between 0.1 and 10. For example, the K value can be 1 for continuous kneading production lines, 1.5 for intermittent kneading production lines, and 2 for production lines using special aggregate formulations. The paste mass M is weighed using a weighing scale with an accuracy of 0.01g to ensure the accuracy of the plasticity index Y calculation.

[0075] According to some embodiments of this application, the above-described method for characterizing the plasticity of aluminum carbon paste further includes a parallel test verification step. Two sets of parallel samples are continuously tested for the same output paste, and the relative deviation of the two sets of plasticity index Y values ​​is calculated. When the relative deviation is ≤5%, the test data is deemed valid; when the relative deviation is >5%, the samples are resampled and retested.

[0076] Parallel testing is a crucial quality control step to ensure the reliability of test data. In industrial production, the paste itself has a certain degree of inhomogeneity, and random errors may also be introduced during sampling and filling processes. By continuously testing two sets of parallel samples and calculating the relative deviation of the Y value, abnormalities in the testing process can be effectively identified. A relative deviation ≤5% indicates good consistency between the two test results, and the data is reliable and can be used for process control decisions. A relative deviation exceeding 5% indicates a significant random error in the test, requiring resampling and retesting to eliminate the influence of accidental factors.

[0077] The method for characterizing the plasticity of aluminum carbon paste provided in this application is simple to operate, and operators can complete the operation according to the standardized procedure without long-term experience training. The entire process from high-temperature sampling to outputting the plasticity index Y can be completed within 30 seconds, and the detection efficiency is much higher than that of traditional laboratory analysis methods. Through multiple quality control measures such as averaging of circumferential multi-point scale readings, paste quality correction, cross-sectional area standardization, and parallel test verification, the accuracy, repeatability, and comparability of the test data are guaranteed. As a single numerical quantitative evaluation index, the plasticity index Y can intuitively distinguish the three states of paste: dry, suitable, and viscous, solving the technical problems of strong subjectivity, poor stability, and lack of quantitative data support caused by the industry's long-term reliance on human sensory judgment. The plasticity index Y can be connected to the DCS or MES system of the production workshop to dynamically adjust key process parameters such as asphalt addition, kneading temperature, paste temperature, and mold temperature, realizing digital closed-loop control of paste plasticity.

[0078] In addition, during the actual use of the device, the operator first places the heat insulation sleeve on the outer wall of the cylindrical section 11 of the main detection cylinder, ensuring that the heat insulation sleeve covers the entire outer wall of the cylindrical section 11 to guarantee the temperature stability of the paste during the detection process. Then, the paste that has just completed the kneading operation is taken out from the kneading production line and placed into the detection cylinder within 5 seconds. Under the action of gravity, the paste naturally falls to the bottom of the detection cylinder and fills the internal space of the cylindrical section 11 and the frustum section 12. After the upper cover 2 is closed, the guide wear-resistant bushing around the upper cover 2 contacts the inner wall of the cylindrical section 11, ensuring that the upper cover 2 slides vertically. The operator applies a fixed force F through the force application platform on the top surface of the upper cover 2, and the pressure display 4 displays the current applied pressure value in real time. Under the action of pressure, the upper cover 2 slides downward, the paste is compressed and undergoes plastic deformation, and the internal gas is discharged through the first exhaust port of the upper cover 2 and the second exhaust port of the lower guide rod 3. After the top cover 2 stops sliding, the operator reads the scale values ​​from multiple circumferential markings on the outer wall of the cylindrical section 11 and averages them. After the test is completed, the lower guide rod 3 is pushed upwards, and the limiting plate 31 pushes the paste out from above the testing cylinder, allowing the paste to be removed and weighed. The entire testing process is simple and quick, and can be completed independently by a single person.

[0079] The terms "first," "second," etc., used in the specification and claims of this application are used to distinguish similar objects and not to describe a specific order or sequence. It should be understood that such use of data can be interchanged where appropriate so that embodiments of this application can be implemented in orders other than those illustrated or described herein, and the objects distinguished by "first," "second," etc., are generally of the same class and the number of objects is not limited; for example, a first object can be one or more. Furthermore, in the specification and claims, "and / or" indicates at least one of the connected objects, and the character " / " generally indicates that the preceding and following objects are in an "or" relationship.

[0080] In the description of this application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc., indicating the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application.

[0081] In the description of this application, "first feature" and "second feature" may include one or more of the features.

[0082] In the description of this application, "multiple" means two or more.

[0083] In the description of this application, the first feature being "above" or "below" the second feature may include the first and second features being in direct contact, or the first and second features being in contact through another feature between them.

[0084] In the description of this application, the terms "above," "over," and "on top" for the first feature and the second feature include the first feature being directly above or diagonally above the second feature, or simply indicate that the first feature is at a higher horizontal level than the second feature.

[0085] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0086] Although embodiments of this application have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of this application, the scope of which is defined by the claims and their equivalents.

Claims

1. A device for testing the plasticity of carbon paste for aluminum, characterized in that, include: The main detection cylinder includes a cylindrical section and a frustum section connected below the cylindrical section. The outer wall of the cylindrical section is provided with scale markings arranged along its axial direction. The large end of the frustum section faces upward and is connected to the cylindrical section. The bottom wall of the frustum section is provided with a through hole. The top cover is slidably disposed inside the cylindrical section of the main detection cylinder. The diameter of the top cover is adapted to the inner diameter of the cylindrical section. A guide wear-resistant bushing is provided around the periphery of the top cover. A first exhaust vent is provided in the center of the top cover. The lower guide rod includes a limiting plate and a rod body connected to the limiting plate. The rod body passes through a through hole in the bottom wall of the frustum section and slides in cooperation with the through hole. The limiting plate is disposed inside the main detection cylinder and abuts against the bottom wall of the frustum section. A pressure gauge is disposed on the top surface of the upper cover and is used to detect the pressure value applied to the upper cover.

2. The aluminum carbon paste plasticity testing device according to claim 1, characterized in that, The outer wall of the cylindrical section of the main detection cylinder has multiple scale markings evenly distributed circumferentially.

3. The aluminum carbon paste plasticity testing device according to claim 1, characterized in that, The cylindrical section is equipped with a travel limit block and a locking alarm component. The travel limit block is spaced at a preset distance from the upper end of the cylindrical section. When the upper cover moves to the travel limit block, the locking alarm component triggers an alarm.

4. The aluminum carbon paste plasticity testing device according to claim 1, characterized in that, The lower guide rod is provided with a second exhaust hole that penetrates the limiting plate and the rod body.

5. The aluminum carbon paste plasticity testing device according to claim 4, characterized in that, The diameter of the upper cover is 30mm~200mm, and the diameter of the exhaust hole in the center of the upper cover is 3mm~20mm; the inner diameter of the cylindrical section of the main detection cylinder is 31mm~201mm, and the height of the cylindrical section is 10mm~100mm; the diameter of the lower guide rod is 10mm~100mm.

6. The device for testing the plasticity of aluminum carbon paste according to claim 1, characterized in that, The outer wall of the cylindrical section of the main detection cylinder is fitted with a detachable heat insulation sleeve, which covers the entire outer wall of the main detection cylinder.

7. A method for characterizing the plasticity of carbon paste for aluminum, characterized in that, The method for characterizing the plasticity of aluminum carbon paste using the plasticity testing device according to any one of claims 1-6 includes the following steps: Step 1: Take the paste that has just finished the kneading operation from the self-mixing production line and put the paste into the main detection cylinder within 5 seconds, so that the paste completely fills the internal space of the main detection cylinder. Step 2: Close the top cover, select at least 3 scale points along the outer circumference of the cylindrical section of the main detection cylinder, read the initial scale value X1 of each scale point, and take the arithmetic mean. Step 3: Apply a fixed force F to the paste through the top cover. After the pressure is applied, keep it still until the top cover completely stops sliding. Step 4: After the upper cover stops sliding, select at least 3 scale points along the circumference of the outer side wall of the cylindrical section of the main body detection cylinder, read the termination scale value X2 of each scale point, and take the arithmetic mean. Step 5: Remove the paste from the main detection cylinder and weigh the paste mass M; Step 6: Calculate the plasticity index Y according to the formula Y=K·[M / (F·π·R²)·(X1-X2)], where K is the proportionality coefficient and R is the inner radius of the cylindrical section of the main detection cylinder.

8. The method for characterizing the plasticity of aluminum carbon paste according to claim 7, characterized in that, The fixed force F is 0.1N~150N; the sliding distance of the upper cover is 0~50mm. When the sliding distance of the upper cover exceeds 50mm, the current test is deemed to be invalid and a retest is required.

9. The method for characterizing the plasticity of aluminum carbon paste according to claim 7, characterized in that, The proportionality coefficient K ranges from 0.1 to 10, and the K value is set according to the kneading process of the aluminum carbon production line; the mass M of the paste is weighed using a weighing scale with an accuracy of 0.01g.

10. The method for characterizing the plasticity of aluminum carbon paste according to claim 7, characterized in that, It also includes a parallel test verification step: continuously test two sets of parallel samples of the same discharge paste, calculate the relative deviation of the plasticity index Y value of the two sets, and determine the test data as valid when the relative deviation is ≤5% and resample and retest when the relative deviation is >5%.